Studi Keterkaitan Negara Hukum Dan Kekuasaan Dalam Perspektif Politik Hukum - Nickolaz Boy Regawoge; Siti Aminah Mega Putri; Maria Ulfa; Parningotan Malau (Yayasan pendidikan dzurriyatul Quran, 2026)
Power is closely related to law because power is not only concerned with the instruments of lawmaking, but also includes law enforcement. The synergistic character of law and power, especially in terms of the legality of power, is explained by Mochtar Kusumaatmadja with one phrase,